RISK MANAGEMENT IMPLEMENTATION MODEL IN MODERATING RISK RELATIONSHIP BASED ON INTERNAL AUDIT - Muammar Khaddafi; Mohd Heikal; Falahuddin F (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to examine and analyze the influence of the Internal Audit Position on the Success of Risk Based Internal Audit, the influence of Top Management Commitment on the Success of Risk Based Internal Audit, the effect of Training on the Success of Risk Based Internal Audit, the Effect of Policy Framework on the Success of Risk Based Internal Audit, the Influence of the Communication Process. on the success of Risk Based Internal Audit, the Role of Risk Management Implementation in moderating the relationship between the Influence of Internal Audit Position, Top Management Commitment, Training, Policy Framework, and Communication on the Success of Risk Based Internal Audit.This research makes all inspectors who have a Functional Auditor Position Certificate at the district / city inspectorates in Aceh province as a population and sample. The results of this study indicate that the variables of internal audit position, top management commitment and application of risk management have no effect on the success of risk based internal audit. Meanwhile, training and policy framework variables have a positive and significant effect on the success of risk based internal audit. Communication variables were found to have no effect on the success of risk based internal audit.The moderating role of the risk management application variable is able to moderate the top management commitment, training and policy framework variables on the success of risk based internal audit. Meanwhile, the application of risk management does not moderate the influence variables of the internal audit position and communication variables on the success of risk based internal audit